Electrocatalytic reduction of N2 and nitrogen-incorporation process on dopant-free defect graphene. Issue 1 (29th November 2019) - Du, Yanqiu; Jiang, Cheng; Xia, Wei; Song, Li; Li, Peng; Gao, Bin; Wu, Chao; Sheng, Lei; Ye, Jinhua; Wang, Tao; He, Jianping
Abstract : Defect graphene was developed as an efficient electrocatalyst for the NRR and transformed from dopant-free graphene to N-doped graphene after the NRR. Abstract : The electrochemical reduction of N2 to NH3 under ambient conditions is a promising N2 fixation method, which provides a new technical solution to remedy the limitations of the Haber–Bosch process. Defect engineering is considered an inspiring strategy for strong N2 activation. Herein, we demonstrate the reduction of N2 on dopant-free defect graphene, which was prepared via the molten salt method. Systematic experiments and density functional theory calculation revealed that the defect sites are the unique active sites for nitrogen adsorption and activation. The phenomenon of N incorporation into graphene using the product NH3 from the NRR as the N source has never been reported before. This was thoroughly studied in this study, and thus serves as a unique perspective to illustrate the significance of defect sites in activating N2 .